2020
DOI: 10.3389/fped.2020.605807
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Inflammatory Multisystem Syndrome and Rheumatic Diseases During SARS-CoV-2 Pandemic

Abstract: Globally, the coronavirus disease 2019 (COVID-19), caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), appeared to have a milder clinical course in children compared to adults. As severe forms of COVID-19 in adults included an aberrant systemic immune response, children with chronic systemic inflammatory diseases were cautiously followed. No evidence for a specific susceptibility was identified in this pediatric population. European and US Pediatricians started to notice cases of myocarditi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
46
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(50 citation statements)
references
References 95 publications
(140 reference statements)
3
46
0
1
Order By: Relevance
“…Then, we compared these patients with patients with MIS-C from a review ( 24 ). Laboratory data were compared between our patients and patients with MIS-C in four previous papers ( 8 11 ). The raw data available for 10 patients with MIS-C in Italy and 6 cases of KDSS in Japan were statistically analyzed using the non-parametric Wilcoxon test.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Then, we compared these patients with patients with MIS-C from a review ( 24 ). Laboratory data were compared between our patients and patients with MIS-C in four previous papers ( 8 11 ). The raw data available for 10 patients with MIS-C in Italy and 6 cases of KDSS in Japan were statistically analyzed using the non-parametric Wilcoxon test.…”
Section: Methodsmentioning
confidence: 99%
“…Kawasaki disease is an acute vasculitis that occurs in childhood, and although its etiology is still unknown, it is known that many inflammatory cytokines are elevated. There have been many reports comparing KD and MIS-C, often stating that the two are partly similar but partly different ( 9 11 ). In particular, the overlap with KD shock syndrome (KDSS), which is KD complicated with circulatory failure and/or shock, is being discussed ( 12 , 13 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, autoantibodies were uniquely produced during MIS-C or KD, which supports a contribution of the humoral response to both diseases(8, 11). Finally, a role for genetic factors has been evocated in MIS-C pathogenesis as it seems to occur more frequently in children from Hispanic or African ethnicity(12, 13).…”
Section: Introductionmentioning
confidence: 99%
“…The Verdoni et al study showed that the monthly incidence of KD in an Italian province had increased 30folds (21). The significant inflammatory response of the body to the novel coronavirus alongside the epidemiological studies have been in favor of the theory that suggests COVID-19 as a trigger for the immune system and an etiology for KD's (61)(62)(63).…”
Section: Discussionmentioning
confidence: 99%